Konseling Karir Life Design untuk Meningkatkan Career Adaptability Siswa - Agung Prasetya; Hawinda Widya Fatma; Awalya Awalya; Edy Purwanto (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to obtain empirical data and ensure the effectiveness of life design career counseling techniques on students' career adaptability abilities. The research design used is a true experimental research design with a sample of 24 students selected using random assignment techniques. Data collection using the Career Adapt-Ability Scale (CAAS) instrument which was adapted through a counseling assessment translation procedure. The hypothesis analysis technique used the T-Test and One Way ANOVA method with 95% probability which was analyzed using SPSS Statistic version 26 software. The results showed that life design career counseling was able to improve students' career adaptability. The conclusion is that life design career counseling is effective in increasing students' career adaptability.